A synopsis model for deterministic behavioral specifications of an adaptable agent - Dussadee Praserttitipong (2018)
This paper proposes a deterministic behavioral approach that encompasses a service discovery model addressing service specifications and matchmaking processes. For service specifications, a synopsis of deterministic intention specification is nominated. Instead of using narrative description, the synopsis is formulated based on behavioral specifications and described by graphical representations to enable visual matching between service intention and advertised specifications. Moreover, an inequivalent matchmaking of this synopsis visualization model is also proposed as a means to investigate and assess various essential characteristic matchings between incomplete intention specification and complete service advertisement. © 2007 IEEE.